2021
DOI: 10.3390/biom11060850
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electric Field (PEF) Enhances Iron Uptake by the Yeast Saccharomyces cerevisiae

Abstract: The aim of the study was to investigate the influence of a pulsed electric field (PEF) on the level of iron ion accumulation in Saccharomyces cerevisiae cells and to select PEF conditions optimal for the highest uptake of this element. Iron ions were accumulated most efficiently when their source was iron (III) nitrate. When the following conditions of PEF treatment were used: voltage 1500 V, pulse width 10 μs, treatment time 20 min, and a number of pulses 1200, accumulation of iron ions in the cells from a 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Additionally, this study showed that during gastric and intestinal digestion in vitro, yeasts are lysed and release most of the iron after 1–3 h of the process. In our previous studies, we have shown that iron ions are bound by functional groups present both in the cell wall and in the intracellular structures of yeast [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, this study showed that during gastric and intestinal digestion in vitro, yeasts are lysed and release most of the iron after 1–3 h of the process. In our previous studies, we have shown that iron ions are bound by functional groups present both in the cell wall and in the intracellular structures of yeast [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…What is important, the panelist did not perceive a metallic after-taste which is a serious problem for products enriched with iron salts. The accumulation of iron in yeast may reduce unfavorable changes in taste in food products, since metal ions are associated with the cell organelles [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After 20 h of cultivation in a media containing iron salts, the cultures were treated with a PEF for 20 min at 3 kV•cm -1 with 1 200 pulses of 10 microseconds. Under these optimal conditions, the accumulation of iron ions (200 µg•mL -1 ) in the cells was 157% higher than the control (without the PEF) with a maximum value of 48.01 mg•g -1 dry mass (Nowosad et al 2021). Similar results were obtained when a S. cerevisiae biomass was exposed to a PEF treatment to improve the zinc accumulation in this https://doi.org/10.17221/78/2021-RAE yeast.…”
Section: Impact Of Pef On the Fermentative Activity Of Microorganismsmentioning
confidence: 87%